Mapping the Ethnographic Expedition: A Re-Configuration of the Frobenius Archive - Boshoff, Janus Jacobus (University of the Witwatersrand, Johannesburg, 2023)
This dissertation considers the building and dwelling (archiving) activities of researchers working within archive spaces as intrinsically connected to the treatment of pictorial material as a primary archive source. The report focusses on the cumulative work of a group of researchers at the University of the Witwatersrand, called the Frobenius Working Group (FWG), in relation to the historic activities of and archive material produced by a German archaeological and ethnographic expedition group under the direction of Professor Leo Frobenius that visited southern Africa between 1928 and 1930 (known as the 9th Expedition). By exploring past and present tensions and connections between the landscape and archive, and the activities and working practices of the FWG and the Frobenius expedition, and by closely studying pictorial archive material, the aim of this research is to interrogate whether the archive can be re-configured as a space where active participation can lead to new and alternative interpretations and understandings. The paper is written in a theoretical, reflective, first person narrative and processual style which reflects the researcher’s personal journey and the thinking processes inherent in the work of research, and explores the contents of and access to the physical and online Frobenius archive, the geography of the landscape and the archive, and the modes of research of the 9th Expedition and the FWG. The research project is thus situated within a physical and a conceptual landscape which suggests that research activities can be considered dwelling practices. The application of theoretical frameworks of landscape, place and space, dwelling and building, provides insight into the complexities and possibilities of generating new interpretations of and additions to the archive, and makes a case for archives as spaces of dwelling where activity bridges time and space, and the researcher can become both active viewer and contributor. The dissertation postulates that the archive can be a field of discovery where active participation can generate new material and insights which deepen our connection to landscape and social activity. The archive as dwelling place is considered not just as an external entity but also as dwelling in us. The emphasis is on configuration and dialogue as the mode of dwelling through which we not only make the archive a dwelling place, but ourselves a dwelling place for the archive. Archiving is a dynamic process in which the sources are considered in order to be configured into new orders. This dynamism requires the bridging and fusing of horizons into productive and co creative partners. This research report finds that the archive does not require re-configuring for it is already a re-configured space. The archive marks the beginning of the researcher’s journey which does not only look at history but, through the research activity, contributes to the constant and continual re-configuration of the archive. This journey conforms to processes of living which are temporal and shaped by social interaction and the continual formation of the landscape. In turn, these life processes contribute to the constant re-configuration of the landscape and archive space. By contributing new material, knowledge and understandings, the researcher forms part of the making of history, thereby ensuring the continued growth, life, and relevancy of the archive.
A Research Report submitted to the Department of History, Wits School of Arts, Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Arts, 2023.
Keywords: Frobenius; Dwelling; Research; Archive; Landscape; Reconfigure; Photography; Place; Space; Taskscape; UCTD; SDG-9: Industry, innovation and infrastructure